2018
DOI: 10.1177/1534508418815749
|View full text |Cite
|
Sign up to set email alerts
|

Using Curriculum-Based Measurement to Predict Student Performance on an Eighth-Grade State Reading Assessment

Abstract: The purpose of this study was to investigate the relationship between scores on two common curriculum-based measures (CBMs), oral reading fluency (ORF) and maze, and scores on the previous statewide assessment of reading in Oregon (Oregon Assessment of Knowledge and Skills-Reading/Literature [OAKS-R]). Data obtained from three cohorts of eighth-grade students were used to examine CBM validity, and the relationship between student characteristics and OAKS-R performance. Positive relationships between ORF and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
(97 reference statements)
0
2
0
Order By: Relevance
“…All but five teams of the researchers reported information about students excluded from the sample. Buchsbaum (2013), LeRoux (2012), and Morgan et al (2011), for example, removed students with missing data. Other researchers excluded students who were not monolingual English speakers (Catts, Bridges, Little, & Tomblin, 2008) or SWDs with more significant impairments, many of whom were placed in more restrictive educational environments (Blackorby et al, 2010; Carlisle, 1999; Gwynne, Lesnick, Hart, & Allensworth, 2009; Hood, 2015; Klingner, Vaughn, Hughes, Schumm, & Elbaum, 1998).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All but five teams of the researchers reported information about students excluded from the sample. Buchsbaum (2013), LeRoux (2012), and Morgan et al (2011), for example, removed students with missing data. Other researchers excluded students who were not monolingual English speakers (Catts, Bridges, Little, & Tomblin, 2008) or SWDs with more significant impairments, many of whom were placed in more restrictive educational environments (Blackorby et al, 2010; Carlisle, 1999; Gwynne, Lesnick, Hart, & Allensworth, 2009; Hood, 2015; Klingner, Vaughn, Hughes, Schumm, & Elbaum, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Most studies that included results from high-stakes assessments did not address the use of retests. Hood (2015) and LeRoux (2012) reported that students could retest up to three times and that the students’ best scores were used in their analyses. We also examined the use of test accommodations.…”
Section: Resultsmentioning
confidence: 99%